A NEW and THREATENED INSULAR SPECIES of LANCEHEAD FROM SOUTHEASTERN BRAZIL - Barbo, Fausto E. [UNESP]; Grazziotin, Felipe G. [UNESP]; Sazima, Ivan; Martins, Marcio; Sawaya, Ricardo J. (Herpetologists League, 2012)
We describe a new species of Bothrops from Vitoria Island, off the coast of São Paulo, southeastern Brazil. The new species differs from the mainland coastal populations of B. jararaca mostly in its smaller and stouter body, number and form of scales, and hemipenial morphology. From B. insularis and B. alcatraz, both related species endemic to islands in southeastern Brazil, B. otavioi sp. nov. differs mainly in its body form and number of scales. The new species has the twist common mitochondrial haplotype for mainland populations of B. jararaca, which is also found in B. alcatraz. A mitochondrial genealogy (gene tree) shows the new species nested within the northern clade of B. jararaca. This genealogical pattern can be explained by a recent speciation event for B. otavioi sp. nov. The isolation of insular species of Bothrops from continental ancestor populations are probably related to the same vicariant process, the oscillations of sea level during the Pleistocene. The new species feeds on small hylid frogs, and attains sexual maturity at 388 mm snout-vent length (SVL; males) and 692 mm SVL (females). Bothrops facial sp. nov. is endemic to Vitoria Island, and should be listed as critically endangered because it is known from only a single area (an island), its geographic range covers less than 100 km(2), and there is a projected continuing decline in the quality of its habitat because of increasing human settlement.
Keywords: Atlantic Forest; Bothrops jararaca group; Bothrops otavioi sp nov.; Evolution; Island endemics; Quaternary; Taxonomy